Advances in CT features and radiomics of checkpoint inhibitor-related pneumonitis: A short review - Jie Huang; Xueqin Chen; Bing Xia; Shenglin Ma (Frontiers in Immunology, 2023)
Checkpoint inhibitor-related pneumonitis (CIP) is a complication of immunotherapy for malignant tumors that severely limits the treatment cycles as well as endangers patients’ health. The chest CT imaging features or typing of CIP and the application of radiomics will contribute to the precise prevention, early diagnosis and instant treatment of CIP. This article reviews the advances in the CT features and the application of radiomics in CIP.